A case study on performance and ductility behaviour of splice connection in steel structures - Kollipara, V. Ramana; Rao, T.D. Gunneswara (Journal of Structural Engineering, 2024)
In most cases, the local failure of the connection in a steel framed structure affects the serviceability criteria of the entire structure. Hence, it is necessary to study and understand the behaviour and failure mechanisms of connections used in steel framed structures. In view of this, the paper describes the experimental, theoretical and numerical investigations conducted on the bolted moment end plate splice connection joining Hollow Tubular Sections (HTS). In this study, a four-bolt end plate connection configuration is adopted for the fabrication of splice connection, and also a parametric variation of the dimensional properties of the connection components such as thickness of end plate, diameter of bolt, and thickness of HTS member is considered. In the theoretical analysis, using the stub tee analogy method new design equations are predicted to compute the ultimate moment capacity of the proposed splice connection. In the numerical analysis, the behaviour of end plate splice connection (with the parametric variation) is studied using finite element package ANSYS in detail. Finally, a comparative study is done between the obtained results of theoretical, numerical with the experimental results to validate the accuracy of predicted design equations and the proposed numerical model.